Penerapan Metode Profile Matching pada Proses Penerimaan Siswa Baru MTs N Fillial Jeblog - Fera Tri Wulandari; Ari Wahyono (Universitas Boyolali, 2023)
MTs N Fillial Jeblog Klaten is a place of education where supporting the acceptance of new students still takes a long time or is less efficient in determining whether students are declared accepted or rejected. There needs to be a decision support system that helps schools determine whether students are accepted according to school criteria. With a decision support system designed using the profile matching method, this problem can be resolved by using a computer system that applies the profile matching method to the process of admitting new students, which in the process uses national exam scores, mathematics, Indonesian, English and achievement as assessment criteria. and prospective students who register as an alternative.